2000
DOI: 10.1108/07363760010309546
|View full text |Cite
|
Sign up to set email alerts
|

Regional market segments of China: opportunities and barriers in a big emerging market

Abstract: As one of the big emerging markets, China's enormous population and rapid increase in consumer spending have attracted many multinational corporations (MNCs). Meanwhile, the misconception of China as a homogeneous market often leads to difficulties in assessing market demand and enacting effective strategies. Examines the diversity among Chinese consumers across seven regional markets. Data from a national survey suggest that consumers from various regions are significantly different from one another in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
165
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(174 citation statements)
references
References 12 publications
7
165
0
2
Order By: Relevance
“…While this assumption may have been incited by its history of communism and centralized rule, in reality there are huge variations between regions. This heterogeneity, which means that markets within China are segmented, has been shown for consumers in general, most notably by Cui and Liu (2000) who identified seven different regions. However, it has not been taken into account when it comes to consumers' CSR attitudes and behaviours.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…While this assumption may have been incited by its history of communism and centralized rule, in reality there are huge variations between regions. This heterogeneity, which means that markets within China are segmented, has been shown for consumers in general, most notably by Cui and Liu (2000) who identified seven different regions. However, it has not been taken into account when it comes to consumers' CSR attitudes and behaviours.…”
Section: Introductionmentioning
confidence: 90%
“…Characterized by Cui and Liu (2000) as "emerging markets", our analysis of region-level information showed that, compared to other regions, they score considerably lower averages for GDP, imports, exports, and FDI (in number and monetary amounts; see Appendix 3).…”
Section: Csr Expectation Differences For Local Chinese Firms and Forementioning
confidence: 99%
See 2 more Smart Citations
“…First, the authors selected seven major cities for data collection. Disparities in institutional environment, socio-culture, economic development, and market conditions across China"s regions have significantly affected management, governance and leadership practices of local organizations [35,36]. Therefore, collecting data from the seven cities chosen to represent China"s eastern-coastal and inland regions enabled the author to control for the potential effects of regional disparities and improve the generalizability of the research findings.…”
Section: I. Introductionmentioning
confidence: 99%